Probabilidad de Error en el Campo de Suma de Verificación del Protocolo Ip - Cárdenas C, Roberto; Hernández Suárez, César Augusto; Pedraza Martínez, Luis Fernando (Ingeniería, 2006)
In this article is presented the analisys of the probability of error of the checksumin IP. Initially is described the mathematical operation complement to one, after is presented characteristic of the algorithm of the checksum and the pattern of errors undetected, finally is made a practical test with the analyzer of protocols of network Ethereal and the results are shownThis research has as goal to make a clear and precise analysis of the probability of error that could introduce checksum algorithm of IP and also raises the following question , Is the checksum field really need in the header the IP protocol?